1983
DOI: 10.1080/10862968309547496
|View full text |Cite
|
Sign up to set email alerts
|

Decoding as a Component of Reading Comprehension among Secondary Students

Abstract: Abstract. The Iowa Tests of Educational Development vocabulary test was administered once to ninth graders following standard procedures (ITED-V) and again using the alternate form in which students listened to a tape-recording of items (PROMPTED-V). Word meaning knowledge was controlled by entering the PROMPTED-V score first into a multiple regression equation to predict reading comprehension. The ITED-V score made a significant addition to the prediction equation, suggesting that the ability to decode printe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Methodologically, Shefelbine (1990) pointed out that it is important to test the effects of word reading on vocabulary because poor word reading can confound results from written vocabulary measures. This point is supported by evidence from ninth graders in Hood and Dubert's (1983) study, which found a significant difference between oral vocabulary scores and reading vocabulary scores on parallel forms of a standardized vocabulary test. In addition, two major theories of comprehension relevant to students in fourth and higher grades-the construction-integration model (Kintsch, 1988(Kintsch, , 1998 and verbal efficiency theory (Perfetti, 1985)-include or assume direct effects of word reading on vocabulary.…”
Section: Paths For Which There Was Contradictory or Weak Evidencementioning
confidence: 63%
See 1 more Smart Citation
“…Methodologically, Shefelbine (1990) pointed out that it is important to test the effects of word reading on vocabulary because poor word reading can confound results from written vocabulary measures. This point is supported by evidence from ninth graders in Hood and Dubert's (1983) study, which found a significant difference between oral vocabulary scores and reading vocabulary scores on parallel forms of a standardized vocabulary test. In addition, two major theories of comprehension relevant to students in fourth and higher grades-the construction-integration model (Kintsch, 1988(Kintsch, , 1998 and verbal efficiency theory (Perfetti, 1985)-include or assume direct effects of word reading on vocabulary.…”
Section: Paths For Which There Was Contradictory or Weak Evidencementioning
confidence: 63%
“…Most experimental studies of reading at the high school level have investigated single variables related to reading comprehension, such as background knowledge (e.g., Stahl, Hare, Sinatra, & Gregory, 1991), inference (e.g., Van den Broek, Tzeng, Risden, Trabasso, & Basche, 2001), cognitive and metacognitive strategy use (e.g., Meyer, Brandt, & Bluth, 1980), reading vocabulary (e.g., Nagy, Diakidoy, & Anderson, 1993), and word reading (e.g., Hood & Dubert, 1983). Each of these variables has been found to separately contribute to high school students' reading comprehension, consistent with findings for both younger and older (e.g., undergraduate) students.…”
mentioning
confidence: 99%
“…If the child would not understand the meaning of the word or passage when spoken, then overuse of decoding strategies can hardly be blamed if the child does not understand the written words. In short, a minimal requirement for establishing "word calling" as defined by the assumptions outlined above is the demonstration that the written material being "called" is within the listening comprehension abilities of the child (see Gough & Tunmer, 1986;Hood & Dubert, 1983).…”
Section: The Phenomenon Of "Word Calling"mentioning
confidence: 99%